VSI converter model - as active power filter (2010)
The power active filters have become a viable alternative for controlling harmonic levels in industrial andcommercial applications. This paper discusses the detailed study of the Shunt Power Active Filter structure in derivation. It presents the methodology for modeling and designing of an active power filter in parallel, the study of the dynamic behavior and with an alternative to the switching model of the active filter. The simulations in this paper were supported by the specialized simulation using the software engineering Simulink-Matlab®.